PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN BENEISH RATIO INDEX - Riyanto, Agus; Sulau, Carolinna Patrichia (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
The purpose of this research is to find out the number and percentage of companies that are classified as manipulators, non-manipulators and gray companies in manufacturing companies in the consumer goods industry sub-sector on the Indonesia Stock Exchange for 2019-2021. The population of this study are manufacturing companies in the consumer goods industry sub-sector on the Indonesia Stock Exchange in 2019 to 2021, totaling 70 companies. The sample for this research was taken using a purposive sampling method with the aim of obtaining a sample that fits the criteria the researcher wanted and produced 37 sample companies. The results of the study stated that in 2019 there was 1 company (2.70%) and in 2020 no companies were found that were included in the manipulator group and in 2021 2 companies (5.41%) were found that were included in the manipulator group. In 2019 there were 33 companies (89.19%), in 2020 there were 35 companies and in 2021 35 companies (94.59%) were found to be in the non-manipulator category. In 2019 there were 3 companies (8.11%), in 2020 there were 2 companies and in 2021 there were no companies classified as gray companies.